Pemanfaatan Inovasi Burung Hantu (Tyto Alba) sebagai Pengendali Hama Tikus (Rattus Argentiventer) oleh Anggota Subak di Desa Senganan Kecamatan Penebel KabupatenTabanan - AZIZ FATHUR ROHMAN; I DEWA GEDE RAKA SARJANA; IGAA LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
Utilizationof Owl Innovation (Tyto alba) as Rat Pests Controller (Rattus argentiventer) by Subak Members in Senganan Village, Penebel Sub-District, Tabanan Regency Rat pest control must be carried out in an integrated and sustainable way. One ofthesolution is to use owls because it does not create pollution and damage to rice plant.Pets controlusing an owl is determined by the knowledge and behavior of subakmembers. The purposes of this study is to determine the adoption process and therelated factors in the use of owl as rat pets control of rets. The research locations waslocated in Senganan Village, Penebel Sub-District, Tabanan Regency using 35respondents. The method used study is qualitative descriptive analysis andordinalmeasurement score. The result showed that level of knowing of respondents was in thehigh category with a score of 422. Pespondents’ persceptions were categorized as goodwith a score of 401. Pespondents’ behavior was categorized as very supportive with ascore achievment of 451.Respondents’ attitudesupporting innovation was 91,43%, whilethosewho were doubtful was 8,57%. The process of adopting subak members hasarrived at the confirmation stage. In the confirmation stage, subak members support thesustainability of innovations applied in subak.Factors relatedto the use of innovationaresuperiority of innovation in the economy and social aspects of subak members, thesuitability of innovation with the environment and the needs of subak members, and theease of technical innovation. Although the number of rets in Senganan Village hasdecreased, subak members still need to preserve the existence of owl, especially inquarantine areas.